The complete book of spaceflight : from Apollo 1 to zero gravity - Darling, David J. (Hoboken, N.J. : Wiley, 2003)
Provides information about the history and principles of spaceflight, covering topics including manned and unmanned missions, fictional portrayals of space journeys, and ideas for future interplanetary missions.
Exponential notation -- Orbits -- Units -- Spaceflight entries A-Z -- Acronyms & abbreviations.
Includes bibliographical references (pages 504-512) and index.
Also issued online.
Keywords: Space flight -- Encyclopedias; Outer space -- Exploration -- Encyclopedias; Exploration of outer space; Space flight; Outer space; Geschichte; Raumfahrt; Encyclopedias; Nonfiction; Encyclopedias